Experimental study on a diode-pumped Nd : CTGG solid-state laser - Luo, Dewei. (2009)
This report documents the study and construction of a Diode-Pumped Solid State Laser (DPSSL), using Neodymium (Nd3+) doped calcium tantalum gallium garnet (Nd:CTGG) crystal as the active gain medium. A fiber coupled laser diode operating at a wavelength of 808nm is used as the pump source. A simple two-mirror laser system is constructed and continuous-wave (CW) output operation at a central wavelength around 1064nm is achieved. The report gives a detailed description of the laser construction and alignment process. Various sets of mirrors with different parameters have been used to form the laser cavity. Laser output power is measured using a photo detector. The Output power verses input power curve is plotted and the laser slope efficiency is calculated. And laser output spectrum is measured by an optical spectra meter. Different sets of the results of the laser performance is compared and analyzed.